Bariery i ograniczenia na ścieżce kariery – o trudnej sytuacji Polek na rynku pracy - Rożdżestwieńska, Joanna (Uniwersytet Wrocławski. Wydział Nauk Społecznych. Instytut Socjologii, 2021)
The main aim of the article is to present the various barriers and limitations that women face in the labor market. The starting point is the industrial revolution and women’s unpaid labor. Other important elements discussed in the article are the negative effects of the system transformation, which women still feel today, i.e., fulfilling the dual role of a housewife and an employee. Then, the article presents various barriers that women face in their careers. Terms that are of particular importance in this article are “glass ceiling”, “escalator”, “sticky floor” and “token status”. Another significant aspect is related to the question of power and management. Women who have overcome the limitations and thus sit in managerial positions must always adapt the masculine style of management.
Keywords: feminism; equality; labor market; barriers